SEMBLANZA Y APORTES METODOLÓGICOS DE UN INVESTIGADOR SOCIAL: ORLANDO FALS BORDA - Rojas Guerra, José María (La Sociología en sus Escenarios, 2010)
<!--[if gte mso 9]> lenovo 12.00 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Abstract. Professor Jose Maria Rojas Guerra investigates on the process of construction of the method of the Investigación Accion Participante - IAP - in the work of sociologist Orlando Fals Borda. In November of 2009 he concluded the elaboration of a preface for an anthology of his short texts that was published by the Institute of Political Studies and International Relations - IEPRI of the National University of Colombia. The author elaborated this paper that concentrates in the problem of the scientific and political commitment, so dedicated to the life and work of Orlando Fals Borda. For the Symposium the International of researcher in Social Sciences, supported by the Centro de Estudios de Opinion de la Universidad de Antioquia – CEO – during 1st to the 3 of December of 2010. Basically, he develop the idea that today the word „commitment‟ has been erased of the language of social sciences and even of the arts and Literature. But fifty years ago the „commitment‟ was the measurement of the relation between the thought and the action, the theory and the practice. The „commitment‟ was consubstantial to the life of the intellectual and the artist. The weight of the neoliberal ideology and the globalization of Capitalism have pred-date to us to concepts of apparent valuing neutrality like those of scene, actor, intervention, imaginary, for example. But more than of a long dream, Latin America is waking up of a nightmare and it already begins to meet again itself with the trajectory of his own thought Resumen. El Profesor José María Rojas Guerra indaga sobre el proceso de construcción del método de la investigación acción Participante -IAP -en la obra del sociólogo Orlando Fals Borda. En Noviembre de 2009 concluyó la elaboración de un prefacio para una antología de sus textos cortos que fue publicado por el Instituto de Estudios Políticos y Relaciones Internacionales – IEPRI de la Universidad Nacional de Colombia. El autor elaboró este ensayo que se centra en el problema del compromiso científico y político, tan caro a la vida y obra de Orlando Fals Borda, para el Simposio Internacional de Investigadores en Ciencias Sociales, auspiciado por el Centro de Estudios de Opinión de la Universidad de Antioquia, los días 1º al 3 de diciembre de 2010 al 3 de diciembre de 2010. Básicamente, precisa que hoy la palabra compromiso ha sido borrada del lenguaje de las ciencias sociales e incluso de las artes y de la literatura. Pero hace cincuenta años el compromiso era la medida de la relación entre el pensamiento y la acción, entre la teoría y la práctica. El compromiso era consustancial a la vida del intelectual y del artista. El peso de la ideología neoliberal y la globalización del capitalismo nos han retrotraído a conceptos de aparente neutralidad valorativa como los de escenario, actor, intervención, imaginario, por ejemplo. Pero más que de un largo sueño, América Latina está despertando de una pesadilla y ya empieza a reencontrarse con la trayectoria de su propio pensamiento.